Global University Rankings and the Mediatization of Higher Education - Stack, Michelle; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Higher Education Institutions simultaneously critique and participate in national and international rankings of universities. However, this creates a difficult situation since if universities do participate in rankings they acquiesce to a system based in media logics that has little to do with academic norms of research. If they do not participate in the rankings they risk losing public funding, students and donors in an increasingly competitive and globalized environment. This book delves into the influence of journalists, business tycoons and multinational corporations in defining what world class is and how it will be measured. Rankings provide us with a rich study for understanding how universities define, deploy and manage their assets and liabilities in a mediatized globalized economy.
Keywords: Communication; Education, Higher; Education and state; Social media; Media and Communication; Higher Education; Education Policy; Social Media; Sociology of Education; Sociology of Education